2018
DOI: 10.11591/edulearn.v12i3.4526
|View full text |Cite
|
Sign up to set email alerts
|

The Students’ Ability to Solve Realistic Mathematical Problems through Polya Type Problem Solving Learning Model

Abstract: This study was done to analyze the effect of Polyatype problem solving learning oriented toward realistic mathematics on the ability to solve mathematical word problems. This study belongs to an experimental research with the Posttest Only Control Group Design. The population used in this study was the students of grade 4 at Gugus VIII SukawatiGianyarelementary schools with the total number of 138. The sample was selected through random sampling. The result of selection by lottery assigned Grade 4 students of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…(2) agencies that provide professional education in measuring the competence 040019-5 of students who will graduate may also use this instrument. (3) The agency that will hold the selection to get novice teachers can also use this instrument to determine social competence. (4) further development of the social competency instruments of teacher candidate students in the field of teacher training is the development of instruments for special field of study education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) agencies that provide professional education in measuring the competence 040019-5 of students who will graduate may also use this instrument. (3) The agency that will hold the selection to get novice teachers can also use this instrument to determine social competence. (4) further development of the social competency instruments of teacher candidate students in the field of teacher training is the development of instruments for special field of study education.…”
Section: Discussionmentioning
confidence: 99%
“…In preparing the items of a good instrument, it is necessary to conduct a theoretical study which is then followed by a factor analysis. The results of the factor analysis will show the quality of the instrument [3].…”
Section: Introductionmentioning
confidence: 97%
“…Polya telah memperkenalkan empat fasa sebagai prinsip dalam penyelesaian masalah. Model ini diguna secara meluas dalam proses penyelesaian masalah [9]. Menurut Prahani, Limatahu, Yuanita, & Nur [10], Model Polya membolehkan pelajar untuk menerangkan proses, merancang dan akhirnya membangunkan proses berfikir dan kemahiran fleksibel yang boleh menjadi pemacu dalam menyelesaikan masalah.…”
Section: Pendahuluanunclassified
“…The results of previous research conducted by Widiana et al (2018) concluded that the use of the Polya-type problem-solving learning model provides better results compared to conventional learning models so the use of the Polya-type problem-solving learning model has a positive influence on problem-solving ability. In addition, research conducted by Sepriyanti et al (2020) concluded that the ability of students who use Polya steps to solve math problems gives better results than students who do not use Polya steps.…”
Section: Introductionmentioning
confidence: 97%